Perception of entomophagy as a healthy food alternative in Panama - Collantes, Rubén (2022)
Objective. To determine the perception of entomophagy as a healthy foodalternative in Panama. Methods. A non-probabilistic sampling was carriedout, targeting 100 people between 18 and 65 years of age, with an educational level of secondary school or higher, a 1:1 ratio of men and women, residents of urban and peri-urban areas, 44% of whom were public servants. An electronic form was shared with them with the following questions: what insects do youknow that are edible, what benefts do you know about the consumption ofinsects, have you ever eaten insects, would you include insects in your diet,why yes or no would you include them? The data were analyzed with Microsoft Excel and PSPP programs. Results. Fifty-eight percent of respondents were aware that crickets and grasshoppers are edible; 45% recognized protein and other nutrients as healthy benefts of eating insects, but a similar percentage were unaware of these benefts; 20% said they had eaten insects at some time and 25% would include them in their diet. Culture, disgust and lack of interestwere the main reasons why the majority discouraged the consumption of insects, while those who would eat insects would do so to improve theirhealth, to try new things and if they are well prepared. The K-means clusteranalysis formed 11 groups, with group 9 standing out as the ideal consumer.Conclusions. To improve the perception of entomophagy as a healthy food alternative in Panama, it is necessary to better educate people and innovate in the processing of food prepared with insects.